JILBAB AS AN ACCESSORY IN THE MODERN ERA AND HIS VIEW ON HADITH - Siddik Firmansyah (Universitas Islam Malang, 2022)
Hijab has become phenomenal with style and fashion in today's modern era without paying attention to a rule in religion to use it properly. The purpose of this study aims to provide a religious rule in using the hijab for Muslim women with a contemporary form according to the Shari'ah. This method uses descriptive-comparative analysis of the hadith. The results in this paper provide enlightenment to the younger generation of Muslim women using the hijab today, still under the auspices of the religious process and the need for religious education from the family, social environment, and culture to filter the use of the hijab according to Islamic religious regulations. In the hadith of the prophet, it is explained that covering the genitals is an obligation for women when at home, dealing with the opposite sex, and when leaving the house, these three things have their hijab limitations for Muslim women in wearing them.